Ensuring fair trade in RMG sector - Rahman, Shahidur (BRAC University, 2014)
The writer is an Associate Professor of Sociology at BRAC University and author of 'Broken Promises of Globalization: The Case of the Bangladesh Garments Industry' published by Lexington Books.